Plant species diversity in a neotropical wetland: Patterns of similarity, effects of distance, and altitude - Bao, Francielli [UNESP]; Leandro, Thales D. [UNESP]; Da Rocha, Maíra; Dos Santos, Vanessa S.; Stefanello, Thiago H.; Arruda, Rafael; Pott, Arnildo; Damasceno-Júnior, Geraldo A. (FapUNIFESP (SciELO), 2018)
The Brazilian Pantanal is an extensive wetland with heterogeneous habitats, primarily due to the riverfloodplain system and plants with differential adaptations and reproductive strategies. Factors such as altitude, distance among plant formations, and flood pulse must be considered to better understand its diversity. Aiming to assess the influence of biogeographic patterns in this system, we analyzed the floristic composition of six areas along the Paraguay River, including residual relieves, verifying the pattern of similarity, and effects of distance and altitude. We recorded 356 species in 87 families, mostly perennial (75%), and some annuals (15%) and pluriannuals (5%). Herbaceous plants were the most represented (48%), followed by arboreal (23%), shrubby (15%) and epiphytic (14%) habits, only 12% being endemic to Brazil. The studied areas showed low floristic similarity, but higher resemblance of species between neighboring areas, and no relation with altitude. The upper Paraguay River is diverse, with high spatial variability of species, predominantly perennial. The river-floodplain connectivity may be a determinant factor in species richness and occurrence of endemic species.
Keywords: Biogeography; Floodplain; Floristics; Pantanal; Vegetation